Analyzing Filipino migrant workers' access to social protection - Aubrey D. Tabuga; Anna Rita P. Vargas; Maria Blesila D. Mondez (Philippine Institute for Development Studies (PIDS), 2021)
The COVID-19 pandemic has such a wide-reaching and sudden adverse impact on people's livelihoods. For a country like the Philippines which significantly relies on overseas remittances to boost household consumption, the return of hundreds of thousands of OFWs is a great reminder of the need for social protection and resilient sources of livelihood. This study examines the access of OFWs to social protection on-site and after they have returned. The objective is to draw useful insights for improving related efforts for ensuring OFWs are protected while working overseas and that the temporary income generated from it aids in building up their resilience when they return to the country for good. The study shows that the most common benefits received by OFWs in their first migration experience are those which meet rather immediate on-site needs than those that are considered as safety nets that allow them to smoothen consumption in times of shocks. Basic worker benefits like health insurance, overtime pay, paid sick leave, and work accident compensation are less common. In fact, only a little over one-half of all workers have health insurance/medical allowance benefits (53%). Only half of the workers received payment for overtime work in their first overseas job. Some 45 percent have received compensation for work accidents. Interestingly, only around 39 percent have been paid for sick leaves. These show the urgency of effective mechanisms for dialogue with host country governments to ensure that OFWs obtain adequate workers' benefits while working abroad. With respect to accessing social protection, the findings point to the need to target the less educated migrant workers and those who hold elementary occupations in all initiatives related to the improvement of awareness and education campaigns on social protection as these workers have the lowest membership to basic social protection schemes. It is also important to note that such vulnerable workers are also in the bottom income classes. Government agencies mandated to promote the welfare of migrant workers must carry out more aggressive steps towards the inclusion of OFWs in social insurance. These may conduct assessments of the current mechanisms being utilized in securing overseas employment certificates and other such mechanisms with respect to their (in)ability to promote access to social insurance. Other initiatives such as education programs related to financial literacy are also important in the effort to increase the willingness and commitment of migrant workers to regularly contribute to insurance schemes for their own protection.
Keywords: 330; social protection; migrant workers; overseas Filipino workers; resilience; social insurance; migrant worker's welfare